Guide to supporting agricultural NDC implementation: GHG mitigation in rice production in Vietnam - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
This document details the process for engaging national partners and supporting agricultural NDC implementation by demonstrating the roadmap for NDC implementation and showcasing ready-made tools and methodologies to support this process.